History, Desire, and Sadomasochism in Alice Munro’s "The Beggar Maid" - Bao, Yuhui (Anthropoetics, 2021)
Alice Munro’s “The Beggar Maid” (1978) dramatizes the romantic trajectory of its lower-class protagonist Rose in mid-twentieth-century Canada, offering insights into the operation of what Mimetic Theory and Generative Anthropology have analyzed as mimetic desire. Emerging from an initially triangular dynamic, Rose’s relations with her wealthy fiancé Patrick descend into what René Girard describes as pathological sadomasochism. My study traces the subtly destructive results of Rose’s aspirations on her love, marriage choice and identity-shaping in an attempt to better understand the ambiguous power of mediated desire in an age of opportunity.